Ecuadorian university ’s chiaroscuro: the challenges In the context of the COVID-19 pandemic - Araujo Silva, Lorena Elizabeth (2020)
The Higher Education Institutions (HEI) temporarily closed its headquarters in order to make a transition from a presence-based modality to an Emergency Remote Teaching due to COVID-19 pandemic. The article’s objective is to analyze the Ecuadorian case in the implementation of this modality, acknowledging it is not automatic rather it hampers the struggled context where the HEI have unsolved issues previous to the pandemic. This document focuses on a literature review and a historical approach on the transformation of Ecuador’s higher education policies by taking as a starting point the first evaluation of universities of 1988 in order to determine the prevailed challenges to implement the Emergency Remote Teaching, after twenty years. The paper develops as follows: (1) First, the article describes brief characteristics of the Emergency Remote Teaching; (2) Second, the paper problematizes the unsolved structural challenges; (3) Finally, the document raises the immediate challenges of HEI in the transition to an Emergency Remote Teaching. At the end, this research concludes that the ability of HEI to adapt themselves to an Emergency Remote Teaching depends to what extent the unsolved structural challenges are sorted out.